Loss of Arf4 causes severe degeneration of the exocrine pancreas but not cystic kidney disease or retinal degeneration. - Jillian N Pearring; Jovenal T San Agustin; Ekaterina S Lobanova; Christopher J Gabriel; Eric C Lieu; William J Monis; Michael W Stuck; Lara Strittmatter; Samer M Jaber; Vadim Y Arshavsky; Gregory J Pazour (PLoS Genetics, 2017)
Arf4 is proposed to be a critical regulator of membrane protein trafficking in early secretory pathway. More recently, Arf4 was also implicated in regulating ciliary trafficking, however, this has not been comprehensively tested in vivo. To directly address Arf4's role in ciliary transport, we deleted Arf4 specifically in either rod photoreceptor cells, kidney, or globally during the early postnatal period. Arf4 deletion in photoreceptors did not cause protein mislocalization or retinal degeneration, as expected if Arf4 played a role in protein transport to the ciliary outer segment. Likewise, Arf4 deletion in kidney did not cause cystic disease, as expected if Arf4 were involved in general ciliary trafficking. In contrast, global Arf4 deletion in the early postnatal period resulted in growth restriction, severe pancreatic degeneration and early death. These findings are consistent with Arf4 playing a critical role in endomembrane trafficking, particularly in the pancreas, but not in ciliary function.